Statistics of poor relief in England and Wales for the year 1851, compiled from the fourth annual report of the Poor Law Board - Cheshire, Edward (Dublin Statistical Society, 1853)
The expenditure for the relief of the poor in England and Wales during the year ended Lady-day, 1851, amounted to #4,962,704, being a decrease of #432,318, or 8 per cent, as compared with the expenditure of the preceding year. The sum expended in the year ended Lady-day, 1851, amounted to 5s. 6d. per head on the population, and in the preceding year to 6s. 1d., being a decrease of 7d. per head. In two counties a small increase has taken place in the expenditure of 1851, as compared with that of 1850; but in all the other counties there has been a decrease.
Read before the Dublin Statistical Society, on Monday, March 21st, 1853
Keywords: Statistics; Welfare; England; Wales; Poor relief; 314.15